The Use of Domino Card Media to Improve Student Learning Outcomes in Natural Science Learning at MIS Mawu - Nurmalah; Juhraeni (MANDAILING GLOBAL EDUKASIA, 2025)
The results of students' science learning are still very low when viewed from the results of daily tests that have been held four times, namely the average is 6.45, this means that it has not met the KKM for science subjects, which is 6.7. The factors causing low student learning outcomes are the teaching methods applied by teachers tend not to activate students, teachers never use media during learning so that students are not interested and not motivated to participate in learning. To solve the above problems, researchers use domino card media in learning. This study aims to determine the impact of using domino card media on improving the science learning outcomes of class III students of MIS Mawu, Ambalawi District, Bima Regency in the 2022/2023 academic year. The method used in this study is classroom action research. PTK is action research carried out with the aim of improving the quality of learning practices in the classroom. The subjects in this study were 39 class III students of MIS Mawu. The type of data used in this study is quantitative data. Where quantitative data is data obtained from student learning outcome data for each evaluation. Data was collected using a learning outcome test. The results of the study showed that the average student learning outcomes in cycle I were 65.00 and had not met the KKM for science subjects and in cycle II the average student learning outcomes increased to 75.12 and had met the KKM for science subjects. Thus, it can be concluded that the use of domino card media can improve the science learning outcomes of class III students of MIS Mawu, Ambalawi District, Bima Regency in the 2022/2023 academic year.